2015
DOI: 10.1016/j.bbrc.2015.03.171
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of inflammation in the ApoE -/- mouse model of atherosclerosis with IodoDPA

Abstract: Background Atherosclerosis is a common and serious vascular disease predisposing individuals to myocardial infarction and stroke. Intravascular plaques, the pathologic lesions of atherosclerosis, are largely composed of cholesterol-laden luminal macrophage-rich infiltrates within a fibrous cap. The ability to detect those macrophages non-invasively within the aorta, carotid artery and other vessels would allow physicians to determine plaque burden, aiding management of patients with atherosclerosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…ApoE −/− mouse model was chosen to explore atherosclerosis because it is a well-established animal model where all recognized stages of atherogenesis could be observed. [11][12][13] Moreover, the complexity and morphological characteristics of atherosclerotic lesions developing in the animal model are very close to those in human. 14 In ApoE −/− mice, atherosclerosis is driven by the impaired clearance of cholesterol-enriched lipoproteins, leading to elevated levels of atherogenic remnants and plasma cholesterol.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…ApoE −/− mouse model was chosen to explore atherosclerosis because it is a well-established animal model where all recognized stages of atherogenesis could be observed. [11][12][13] Moreover, the complexity and morphological characteristics of atherosclerotic lesions developing in the animal model are very close to those in human. 14 In ApoE −/− mice, atherosclerosis is driven by the impaired clearance of cholesterol-enriched lipoproteins, leading to elevated levels of atherogenic remnants and plasma cholesterol.…”
Section: Introductionmentioning
confidence: 68%
“…Mice lacking Apolipoprotein E (ApoE) can develop hypercholesterolaemia and atherosclerosis, more pronouncedly under the induction of high‐fat diet. ApoE −/− mouse model was chosen to explore atherosclerosis because it is a well‐established animal model where all recognized stages of atherogenesis could be observed . Moreover, the complexity and morphological characteristics of atherosclerotic lesions developing in the animal model are very close to those in human .…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 18 F-FDG uptake was found to correlate positively with macrophage density (23). TSPO ligands such as 125 I-DPA-713 (N,N-diethyl-2-(4-methoxyphenyl)-5,7-dimethylpyrazolo[1,5-a]pyrimidine-3-acetamide) (24) and 11 C-PK11195 (25), as well as labeled DOTATATE ( 68 Ga and 64 Cu) (Fig. 3) (26), have also been used in the evaluation of plaques.…”
Section: Imaging Of Inflammation At the Organ Levelmentioning
confidence: 99%
“…Atherosclerotic lesions, an abnormally thickened intima-media layer, and vascular thromboses may be directly imaged with high resolution ultrasound (Choudhury et al, 2004; Chatterjee et al, 2014; Zhang et al, 2015) and also enhanced with specific contrast agents (Wang et al, 2012; Foss et al, 2015). Arterial stiffness may be determined by the pulse wave velocity (Hartley et al, 2011; Chatterjee et al, 2014) or a combination of aortic diameter and invasive blood pressure measurements (Kuo et al, 2014); for a more precise determination of localized arterial wall characteristics, pulse wave imaging has more recently been developed (Fujikura et al, 2007; Nandlall et al, 2014).…”
Section: Vascular Imaging: Ultrasoundmentioning
confidence: 99%